2015
DOI: 10.1371/journal.pone.0115894
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Patterns of People Affected by Depressive and Anxiety Disorders as Measured by Accelerometers: A Cross-Sectional Study

Abstract: BackgroundExercise can relieve both depressive and anxiety disorders and it is therefore of importance to establish movement patterns of mildly to moderately affected sufferers to estimate the treatment potential. The aim is to describe the physical activity patterns of people affected by mild to moderate depressive and/or anxiety symptoms using objective measures of physical activity.MethodsThe design of the study was cross-sectional using data from 165 people aged 18–65 years, with mild to moderate depressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 31 publications
8
78
3
Order By: Relevance
“…9,10 However, there is a lack of clarity about these results, due to the cross sectional nature and the directionality of the association, since depression is characterized by fatigue and asthenia, which may themselves lead to a decrease in activity. 11 Other longitudinal studies have reported that low physical performance [11][12][13] is associated with a higher risk of depression in older people suggesting that low physical performance could play a role in the development of depression. Whilst helpful, physical performance data, captured via self-report questionnaires, have poor recall properties, reliability and validity in older adults and might introduce bias.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However, there is a lack of clarity about these results, due to the cross sectional nature and the directionality of the association, since depression is characterized by fatigue and asthenia, which may themselves lead to a decrease in activity. 11 Other longitudinal studies have reported that low physical performance [11][12][13] is associated with a higher risk of depression in older people suggesting that low physical performance could play a role in the development of depression. Whilst helpful, physical performance data, captured via self-report questionnaires, have poor recall properties, reliability and validity in older adults and might introduce bias.…”
Section: Introductionmentioning
confidence: 99%
“…Participants however, found it more difficult to report domain specific sitting time over the last week than physical activity over the same time period which is consistent with our findings of adults with mental illness living in the community 89 . This may be due to the high levels of sedentary behavior in this population 96,100 and that physical activity is more discretely defined and therefore easier to recall than sedentary behavior. This was also reflected in the reporting of extreme values for the sitting time questionnaire in which six participants were unable to answer the questionnaire and of those who did, extreme values were reported by a quarter of participants.…”
Section: Discussionmentioning
confidence: 98%
“…Accelerometer results from a Swedish study of 165 adults with anxiety and depression, indicated an average time of 42 minutes/day in MVPA and 9.1 hours/day in sedentary behaviour 100 . Similarly, accelerometer results from an American study of 81 adults with schizophrenia indicated an average time of 32 minutes/day in MVPA and 8.9 hours/day in sedentary behaviour 101 .…”
Section: Physical Activity and Sedentary Behaviour Among Adults With mentioning
confidence: 99%
“…A large Australian survey (n=1,825) of people receiving mental health services for a psychotic disorder reported that 3.3% of respondents were moderately active according to the scoring rules of the IPAQ (three or more days of vigorous activity, or five or more days of at least 600 MET-min/week) 25 . One study assessing the psychometrics of the IPAQ- [209][210][211][212] , and SB ranging from 9.1 to 13.5 hours/day [209][210][211] . These studies have typically focused on samples of adults with one specific psychiatric diagnosis, such as schizophrenia 211 , depression and/or anxiety 210 , and bipolar disorder 209 ; one study was with adults across a range of mental health diagnoses 212 .…”
Section: Physical Activity and Sedentary Behaviour In Adults With Menmentioning
confidence: 99%
“…One study assessing the psychometrics of the IPAQ- [209][210][211][212] , and SB ranging from 9.1 to 13.5 hours/day [209][210][211] . These studies have typically focused on samples of adults with one specific psychiatric diagnosis, such as schizophrenia 211 , depression and/or anxiety 210 , and bipolar disorder 209 ; one study was with adults across a range of mental health diagnoses 212 . Two studies also assessed bout durations of SB and MVPA, which may have different health-related implications to total accumulated time 157,213 : one found that adults with depression and/or anxiety accumulated 42% of SB in ≥20 minute bouts, and 43% of MVPA in ≥10 minute bouts 210 ; the other found that only 4% of a sample of adults with mental illnesses who had accumulated at least 150 minutes/week of MVPA, did so in ≥10 minute bouts 212 .…”
Section: Physical Activity and Sedentary Behaviour In Adults With Menmentioning
confidence: 99%